Soil aggregation according to the dynamics of carbon and nitrogen in soil under different cropping systems - Seben Junior, Getulio de Freitas (2016)
The objective of this work was to evaluate total soil carbon and nitrogen, as well as their contents in particulate and mineral-associated C fractions; to determine C stock and sequestration rates in the soil; and to verify the effect of C and N contents on soil aggregation, using different crop rotations and crop sequences under no-tillage. The study was carried out for nine years in a clayey Oxisol. The treatments consisted of different cropping systems formed by the combination of three summer crops (cropped until March) corn (Zea mays) monocropping, soybean (Glycine max) monocropping, and soybean/corn rotation and seven second crops (crop successions). Soil samples were taken at the 0.00-0.10-m layer for physical fractionation of C and N, and to determine soil aggregation by the wet method. Soybean monocropping increased C and N in particulate C fraction, while the crop systems with corn monocropping x pigeon pea (Cajanus cajan), corn monocropping x sun hemp (Crotalaria juncea), and soybean monocropping x corn as a crop succession increased total C in the soil. Greater rates of soil C sequestration were observed with soybean/corn rotation and with soybean monocropping, as well as with sun hemp as a second crop. The increase in total N increases soil C stock. Soil aggregation was most affected at particulate C fraction. Increases in soil N promote C addition to particulate fraction and enhance soil aggregation.